The Analysis of Amount and Various Age of Productive Female Bali Cattle that Slaughtered at Abbatoirs - I Wayan Suardana; I Made Sukada; I Ketut Suada; Dyah Ayu Widiasih (Jurnal Sain Veteriner, 2013)
Abstract Base on the ability for surviving at the limited vegetations, bali cattle is famous  as a pioneer cattle.  Although the fertility of Bali cattle has  known   so high (up to 80%), but  the slaughter  of productive  female  of bali cattle from year to year is so high too, so that the existance of Bali cattle in the future is threatened extinct. The accurate data  indicating  the amount of Bali cattle slaughtered  at  the abbatoirs are  not available yet, exactly from the Pesanggaran and Mambal  abbatoirs as  the bigger abbatoirs in Bali.  The study used 246 heads of  Bali cattle originated from Pesanggaran, and 232 heads of  Bali cattle originated from Mambal abbatoirs, respectively. The study indicated as many as   81,7%, and 87,5% of Bali cattle slaughtered  at  those abbatoirs  were female. According to their  ages, most of them were  productive too, i.e.  99% at Pesanggaran, and 67,49% at Mambal abbatoirs, respectively. These  result  indicated  it is needed a  special attention from the Bali government exactly from the Animals Husbandry Officer in order to prevent the loss of Bali cattle populations  in the future.